Modeling of long-cable-fed induction motor drive system for predicting overvoltage transients - Wang, L.; Jatskevich, J. (Energy and Automation, 2015)
Induction motor drive systems fed with cables are widely used in many industrial and agricultural applications. Accurate prediction of motor terminal overvoltage, caused by impedance mismatch between the long cable and the motor, plays an important role for motor dielectric insulation and optimal design of dv/dt filters. In this paper, modeling methodology for the investigation of long-cable-fed induction motor drive overvoltage is proposed. An improved high-frequency motor equivalent circuit model is developed to represent the motor high-frequency behavior for the time- and frequency-domain analyses. A high-frequency cable model based on improved high-order multiple-p sections is proposed. The proposed methodology is verified on an experimental 2.2 kW ABB motor drive benchmark system. The motor overvoltage transients predicted by the proposed model is in excellent agreement with the experimental results.